New cholesterol management guideline 2013: a review - Fattah, Sk Abdul; Saha, Aloke Kumar; Alam, Md Towhid; Ali, Md Yusuf (Faridpur Medical College Journal, 2015)
Management of high blood cholesterol is the key point for the treatment and prevention of Atherosclerotic Cardiovascular Disease (ASCVD). Till 2013, Adult Treatment Panel III (ATP III) report was the guideline for the physician for blood cholesterol management. The main feature of this guideline was to achieve a particular target cholesterol level by lifestyle modification, dietary changes and lipid-lowering drugs. But the recently released American College of Cardiology (ACC) and American Heart Association (AHA) guidelines shifted attention to Statin use at high-, moderate- or low-intensity instead of chasing a cholesterol goal. This article reviews the main features of this new guideline comparing to the previous one, where appropriate. Faridpur Med. Coll. J. 2014;9(1): 42-45